First-Time Chinese Online Students’ Expectations of Their Instructors in Fully Online Learning Environments - Lin, Xi (Online Learning, 2022)
The global COVID-19 lockdowns caused universities to shift from face-to-face instruction to online. Since online teaching was used as a supplement to the traditional in-person instruction before the pandemic in China, Chinese college students were forced to learn in fully online learning (FOL) environments with very little preparation. These first-time online students faced challenges that significantly impacted their confidence and ability to succeed as online learners. Fortunately, the instructor can play a crucial role in conducting early interventions to reduce students’ online learning anxiety but understanding these students’ expectations of their online instructor is necessary for using appropriate teaching strategies. As a result, this study investigates 439 first-time Chinese online students’ expectations of their instructor in FOL environments during the emergent transition. Results indicate that several characteristics are highly expected by new online Chinese learners, such as being familiar with technology, being knowledgeable about the subject, and respecting other students. This study is expected to point Chinese universities and others toward best practices in preparing their faculty members for online course instruction, thus further enhancing first-time online students’ learning experiences.